Teaching Computational Thinking Main Concepts with a Marble-Powered Computer - Quintela, Barbara M.; Guimarães, Maria Luísa R.; Dias, Lara da Silva; Verly, Ana Clara; Oliveira, Alessandreia (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2025: Anais do V Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2025.5330, 2025)
This paper presents an activity aimed at teaching the main concepts of Computational Thinking to high school students. Algorithmic structures such as conditionals and loops are presented playfully using a game that represents a marble-powered computer. The activities described herein were applied to two groups of 21 and 16 high school students during 40-minute sessions. Besides describing the activity, it is also discussed how it could be extended to cover the main necessary concepts related to Computational Thinking. Results show that the students were quickly engaged in the activity, and even with the short time, most of them were able to understand the concepts and solve the challenges, indicating it could be an interesting approach.